Polarized upconverting luminescence in a liquid crystal polymer network/upconverison nanorods composite film. (3rd July 2018) - Ye, Simin; Gao, Jingjing; Juan, Ao; Guo, Jinbao
Abstract: A polarized upconverting luminescence in a novel upconverison nanorods (UCNRs)/liquid crystal network polymer (LCN) composite film is proposed. The UCNRs were fabricated by hydrothermal method, which were further modified to be introduced into LCN precursors with good dispersion. The orientation of UCNRs in LCN precursors was found to be strongly influenced by the configuration of LC molecules which could be modulated by external electric field. The UCNRs/LCN composite films in planar and homeotropic configuration were fabricated by UV photopolymerization. It is demonstrated that upconverting fluorescence emission from the UCNRs/LCN film with planar orientation is polarization-dependent, while the emission from the UCNRs/LCN film with homeotropic alignment is not polarized. These observations are ascribed to the directional arrangement of the UCNRs enabled by the LC molecules alignment and the crystal symmetry of the UCNR matrix. This work paves a different avenue to the construction of the upconversion nanoparticles/polymer composite system with prospective application value in anti-counterfeiting optical films.